FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN FRAKTUR PRE OPERASI - Siska Oktarini; Rezi Prima (STIKes Al-Insyirah Pekanbaru, 2021)
Surgery is a condition that can cause anxiety, anxiety that occurs in different fracture patients. Decreasing anxiety is important, because anxiety can increase the risk of surgery. The purpose of this study was to determine the factors associated with the level of anxiety in preoperative fracture patients. The design of this research is analytic descriptive, with a cross-sectional approach. The sampling technique was Accidental Sampling, with a sample size of 31 respondents. The statistical test used the Chi-Square test with a significant level (α = 0.05). The results showed that more than half (61.3%) had a severe level of anxiety, more than half of 61.3% were male, more than half (64.5%) had low education, mostly (80.6%). ) have low economic status, and more than half (67.7%) have poor family support. Based on the statistical test of the relationship between gender variables, it was found that there was no relationship between gender and anxiety levels (p=0.274), there was a relationship between education and anxiety levels (p=0.007), there was a relationship between economic status and anxiety levels (p=0.022) , there was no significant relationship between family support and the level of anxiety (p=0.127). From the results of this study, it is hoped that the respondent can provide input in order to find out what are the factors that can affect the level of anxiety and the respondent can maintain the mindset to avoid excessive anxiety.